Labour Market Transitions, Shocks and Institutions during the Great Recession: A Cross-Country Analysis - Rahel Felder; Ronald Bachmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper analyses the impact of the Great Recession on labour market dynamics in industrialized countries. Using unique measures of labour market flows constructed from worker-level micro data, we examine to what extent macro shocks were transmitted to national labour markets. Following Blanchard and Wolfers (2000), we focus on the role of the interaction of shocks and institutions for labour market flows - in addition to the unemployment rate - in order to explain cross-country differences in labour market reactions to the Great Recession. Our results show that interactions between shocks and institutions have explanatory power when considering observable macroeconomic shocks; interactions with trade union variables are of particular relevance in this context.
Keywords: J60; E24; J08; 330